2015
DOI: 10.5152/tjg.2014.5949
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial integrated ultrasonic backscatter for early detection of cardiac involvement in patients with Wilson disease

Abstract: Background/Aims: Videodensitometry is a feasible noninvasive ultrasound tissue characterization method allowing early detection of myocardial changes. This study aimed to investigate ultrasonic backscatter properties of the myocardium in Wilson disease patients. Materials and Methods: We compared cardiologically asymptomatic Wilson disease patients (W group) (n=18) with age-matched (26.7±9.6 years) healthy controls (C group) (n=15). Diagnosis of Wilson disease was made on the basis of clinical manifestations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…BRS is a sensitive predictor for worse prognosis in many chronic diseases, especially in heart diseases (La Rovere et al, 1998 ; Pinna et al, 2005 ). Cardiac abnormality is a common finding in Wilson's disease (Factor et al, 1982 ; Hlubocka et al, 2002 ; Arat et al, 2014 ). Factor et al revealed cardiac hypertrophy, interstitial and replacement fibrosis, intramyocardial small vessel sclerosis and focal inflammation in an autopsy study of Wilson's disease, though these changes were not significantly correlated with the tissue levels of copper or the presence of cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…BRS is a sensitive predictor for worse prognosis in many chronic diseases, especially in heart diseases (La Rovere et al, 1998 ; Pinna et al, 2005 ). Cardiac abnormality is a common finding in Wilson's disease (Factor et al, 1982 ; Hlubocka et al, 2002 ; Arat et al, 2014 ). Factor et al revealed cardiac hypertrophy, interstitial and replacement fibrosis, intramyocardial small vessel sclerosis and focal inflammation in an autopsy study of Wilson's disease, though these changes were not significantly correlated with the tissue levels of copper or the presence of cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Arat et al studied 18 patients with WD and found normal LV size and function, and the ECG showed only an increase in the P wave dispersion [37]. In another study from the same group of researchers, the abnormalities in two-dimensional echocardiographic grey-level distributions in patients with WD were described as a result of an early stage of cardiac involvement [38]. In a recently published study Karakurt et al reported that pediatric patients with WD showed diastolic dysfunction and regional deformation abnormalities, especially rotational strain and strain rate abnormalities [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, myocardial integrated ultrasonic backscatter has been reported to detect early changes in myocardium of patients with Wilson's disease. [7]…”
Section: Discussionmentioning
confidence: 99%